PEMANFAATAN MEDIA INTERNET SEBAGAI SUMBER BELAJAR PADA SISWA SMA NEGERI 1 JARAI KABUPATEN LAHAT - Ibrahim Murizal (DIADIK, 2021)
This study aims to determine the use of internet facilities by students of SMA Negeri 1 Jarai Lahat Regency. The internet facilities referred to include the use of sites at SMA Negeri 1 Jarai which are accessed by students with regard to assignments given by the teacher and subject scores. This research is a qualitative research that does not use statistical numerical methods. In this study the researcher is the main instrument (keyinstrument). The essence of the researcher as the main instrument is applied in the use of data collection techniques. Data collection techniques in research methods include: interviews, observation, and documentation. The results of this study describe the function of the internet in the learning process so that students can look for learning resources, extracted materials, the process of improvement that generates new ideas and the factors that influence it